Antibacterial properties of zinc oxide nanoparticles on klebsiella pneumoniae atcc 13883 - Tan, Sin Ty (2022)
The overuse of antibiotics to treat Klebsiella pneumoniae infection has led to the development of multidrug-resistant strains, stimulating the study of the nanomaterial as an effective antibacterial alternative to conventional antibiotics. The objectives of our study were to evaluate the antibacterial activity of ten zinc oxide nanoparticle (ZnO NP) concentrations against Gram-negative bacterium K. pneumoniae by determining growth inhibitory effects via microbroth dilution method, bacterial surface functional groups involved in attaching ZnO NPs to bacteria by Fourier transform infrared (FTIR) spectroscopy, and the morphological alterations caused by ZnO NPs through the scanning electron microscope with energy-dispersive X-ray spectroscopy (SEM-EDX). All the tested ZnO NP concentrations showed statistically significant inhibition against K. pneumoniae in turbidity and INT assays. The average percentage of growth inhibition reported on K. pneumoniae was 5, 13, 17, 23, 29, 36, 46, 65, 83, and 87% for 5, 10, 20, 40, 80, 160, 320, 640, 1280, and 2560 μg/ mL of ZnO NPs, respectively. Besides, the MIC value was determined to be 2560 μg/mL using an iodonitrotetrazolium chloride (INT) assay. The FTIR spectrum exhibited the involvement of bacterial surface polysaccharides, proteins, glycogen, and phospholipids in the interaction of ZnO NPs with bacterial cells. Furthermore, SEM analysis showed ZnO NP aggregation on bacterial cells, roughening of the cell surface, membrane damage and rupture, cell shrinkage and distortion. The EDX analysis verified the adsorption of ZnO NPs on K. pneumoniae surface. The attachment of ZnO NPs to K. pneumoniae and the subsequent morphological damages are the possible causes behind the inhibitory effects of ZnO NPs on K. pneumoniae growth. Overall, our current study confirmed the dose-dependent antibacterial activity of ZnO NPs against K. pneumoniae via the interaction of NPs with K. pneumoniae envelope, which caused alterations in cell membrane integrity that might have resulted in cell death.